Experimental study on the behaviour of granular column-treated soft clay under shear loading. Issue 2 (4th March 2023) - Hosseinpour, Iman; Ghorbani, Ali; Zarei, Javad; Ranjan Mohapatra, Sunil
ABSTRACT: Compacted granular columns are frequently used to mitigate construction difficulties over soft soil deposits through a combination of densification, increasing load-bearing capacity and improvement in consolidation features. The behaviour of granular columns under vertical loading has been well recognised; however, this research is aimed to investigate the behaviour of granular column-reinforced soft soil subjected to shear stress. In this contribution, large-scale direct shear tests were performed, and the influence of undrained shear strength of clay, diameter of granular column and relative density of aggregates was examined. In general, the use of granular column has been shown to improve the shear resistance of the composite ground, which was found to be much significant at lower undrained shear strength of the soft clay. Increasing density of aggregates from Dr = 50% to 90% caused a large portion of the shear stress to be sustained by the accumulated friction of aggregates as the internal friction angle of the treated clay increased from 0 to 28°. In addition, test results revealed that the use of highly compacted column yields a lowered shear displacement at failure, which was indirect evidence of stiffness improvement of the composite ground.